Carbon Offsets with Endogenous Environmental Policy - Strand, Jon (2012)
Interests in obtaining carbon offsets in host countries for Clean Development Mechanism projects may serve as an obstacle to implementing more stringent general environmental policies in the same countries. A relatively lax environmental policy, whereby carbon emissions remain high, can be advantageous for such countries as it leaves them with a higher than otherwise scope for future emissions reductions through Clean Development Mechanism and other offset projects. In this note, the potential to affect the availability of future Clean Development Mechanism projects is shown to distort environmental and energy policies of Clean Development Mechanism host countries in two ways. Measures to reduce use of fossil energy are weakened. Because this weakens private sector incentives to switch to lower-carbon technology through Clean Development Mechanism projects, host governments then also find it attractive to subsidize this switch, in order to maximize the country s advantage from the Clean Development Mechanism.